The Role of Customer Satisfaction Mediates the Effect of Experiential Marketing on Repeat Purchase on Domus Coffee Consumers in Denpasar City - Maki, Gyshella Eunike; Santika, I Wayan (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to examine the role of customer satisfaction in mediating the effect of experiential marketing on repeat purchases among Domus Coffee consumers in Denpasar City. Using a quantitative associative approach, data were collected from 65 respondents through questionnaires and interviews with the coffee shop owner. The analysis was conducted using path analysis, Sobel test, and classical assumption tests with SPSS 26.0. The results show that experiential marketing has a positive and significant effect on repeat purchases and customer satisfaction, while customer satisfaction itself has a positive and significant impact on repeat purchases. Furthermore, customer satisfaction partially mediates the relationship between experiential marketing and repeat purchases, as indicated by a Variance Accounted For (VAF) value of 59.49%. These findings imply that creating memorable and positive experiences not only increases satisfaction but also strengthens consumer loyalty through repeat purchases. This research contributes to enriching the Theory of Planned Behavior (TPB) in the context of the coffee shop industry and provides practical insights for coffee shop managers to enhance competitive advantage by focusing on consumer experiences and satisfaction.